Mongolia in the Foreign Policy of India under Narendra Modi (Journal of International Studies, 2024)
The victory of the Bharatiya Janata Party in the 2014 elections, replacing the long-standing government led by the Indian National Congress, drew the attention of international relations and political science scholars to how India’s foreign policy would change and what direction it would take. Researchers were divided on whether India’s foreign policy would undergo a significant shift or continue the course of previous administrations under the leadership of Narendra Modi. Under Modi’s leadership, India’s foreign policy has focused on economic diplomacy and a strong foreign policy aimed at establishing itself as a powerful nation, not only in the region but also on the global stage.Нарендра Модигийн үеийн Энэтхэгийн гадаад бодлого дахь Монгол УлсХураангуй: Олон жилийн турш Энэтхэгийн Үндэсний Конгрессын нам засгийн газрыг тэргүүлж байсан явдлыг халж 2014 онд Бхарати Жаната нам сонгуульд ялсан нь Энэтхэгийн гадаад бодлого хэрхэн өөрчлөгдөж, хаашаа чиглэх нь олон улсын харилцаа, улс төр судлаачдын анхаарлыг татаж байв. Н.Модигийн удирдлагад шилжсэнээр Энэтхэгийн гадаад бодлого эрс өөрчлөгдөнө, эсвэл өмнөх үеийн бодлогыг үргэлжлүүлэн авч явна гэж судлаачид хоёр талд хуваагдаад байсан юм. Н.Моди Энэтхэгийн гадаад бодлогыг бүс нутагтаа төдийгүй дэлхийд хүчирхэг гүрэн болох байр суурь руу чиглэсэн эдийн засгийн дипломат ажиллагаа, хүчтэй гадаад бодлогыг гарган ирж явуулах болжээ.Түлхүүр үгс: Нарендра Моди, Энэтхэгийн гадаад бодлого, ашиг сонирхол, Монгол Улс, Гуравдагч хөршийн бодлого